Stable isotope fractionation of tungsten during adsorption on Fe and Mn (oxyhydr)oxides. (1st May 2017) - Kashiwabara, Teruhiko; Kubo, Sayuri; Tanaka, Masato; Senda, Ryoko; Iizuka, Tsuyoshi; Tanimizu, Masaharu; Takahashi, Yoshio
Abstract: The similar, but not identical chemical properties of W compared with Mo suggest that the stable isotope system of W could be a novel proxy to explore the modern and ancient ocean as is the case in the well-established utility of Mo isotopes. We experimentally investigated the isotopic fractionation of W during adsorption on Fe and Mn (oxyhydr)oxides (ferrihydrite and δ-MnO2 ), a key process in the global ocean budget of this element. Our adsorption experiments confirmed that W isotopes fractionate substantially on both ferrihydrite and δ-MnO2 : lighter W isotopes are preferentially adsorbed on both oxides as a result of equilibrium isotopic exchange between dissolved and adsorbed species, and the obtained values of Δ 186/183 Wliquid–solid ( = δ 186 Wdissolved  − δ 186 Wadsorbed ) are 0.76 ± 0.09‰ for ferrihydrite and 0.88 ± 0.21‰ for δ-MnO2 (2 σ, n  = 6). Compared with the case of Mo isotopes, fractionation of W isotopes is (i) of comparable magnitude between ferrihydrite and δ-MnO2, and (ii) much smaller than that of Mo on δ-MnO2 . Our previous XAFS observations and newly-performed DFT calculations both indicate that the observed W isotopic fractionations are caused by the symmetry change from Td (tetrahedral) WO4 2− to distorted Oh (octahedral) monomeric W species via formation of inner-sphere complexes on both ferrihydrite and δ-MnO2 . The similar isotopic fractionations between the two oxides relate to the strong tendency for W to form inner-sphere complexes, which causes the symmetry change, in contrast to the outer-sphere complex of Mo on ferrihydrite. The smaller isotopic fractionation of W compared with Mo on δ-MnO2 despite their similar molecular symmetry seems to be due to their different degrees of distortion of Oh species. Our findings imply that the isotopic composition of W in modern oxic seawater is likely to become heavier relative to the input by removal of lighter W isotopes via adsorption on ferromanganese oxides in analogy with the Mo isotope budget. In contrast, the isotopic composition of W in ancient seawater should have evolved in response to the extent of deposition of both Fe and Mn oxides; this is likely to be different compared with that of the Mo isotopes, which is strongly associated with the occurrence of Mn oxides relative to Fe oxides.